2003
DOI: 10.1242/jeb.00298
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional organization of protein kinase signaling cascades: the roles of diffusion, endocytosis and molecular motors

Abstract: SUMMARYExtracellular signals received by membrane receptors are processed, encoded and transferred to the nucleus via phosphorylation and spatial relocation of protein members of multiple component pathways, such as mitogen activated protein kinase (MAPK) cascades. The receptor-induced membrane recruitment of the cytoplasmic protein SOS results in the activation of the Ras/MAPK cascade. It has been suggested that the membrane recruitment of signaling proteins causes an increase in the diffusion-limited rates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
125
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 86 publications
4
125
0
1
Order By: Relevance
“…This termination of signaling by phosphatases necessitates mechanisms to facilitate signal propagation across a cell. In fact, recent experimental and theoretical work showed that endocytosis, scaffolding, molecular motors, and traveling waves of phospho-proteins are involved in the propagation of signals to different cellular locations [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This termination of signaling by phosphatases necessitates mechanisms to facilitate signal propagation across a cell. In fact, recent experimental and theoretical work showed that endocytosis, scaffolding, molecular motors, and traveling waves of phospho-proteins are involved in the propagation of signals to different cellular locations [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, although this scheme is more complicated than the systems discussed so far, it contains many regulatory interactions of the former. This is reflected in the model structure with respect to the rate laws for GTP hydrolysis and GDP→GTP exchange, respectively: (32) Note that for the 3 rd -level GEF we include constitutive activity and activation by the first GTPase.…”
Section: A Device For Sensing Cellular Distancesmentioning
confidence: 99%
“…Although active ERK1/2 translocate to the nucleus (Volmat and Pouyssegur, 2001), mathematical calculations based on diffusion coefficients have anticipated that the rate of nuclear import of the activated ERKs could not be simply explained by diffusion of the cytosolic kinases (Kholodenko, 2003). Association with and movement along the endocytic pathway have therefore been suggested as a reasonable solution for the spatial segregation of the activated ERKs and facilitation of their transport toward the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Since traveling waves propagate with a constant speed, the time of the signal transfer increases linearly with the cell size, whereas the time of signal propagation by diffusion is proportional to the square of the cell size. This is a reason why travelling waves can effectively transfer protein modification signals 47 .…”
Section: Spatial Signaling By Gtpase Cascadesmentioning
confidence: 99%
“…Signaling pathways are spatially organized in living cells. Often, an activating enzyme and opposing deactivating enzyme are localized to distinct cellular structures 26,47 . For instance, activating signals can occur on the plasma membrane or intracellular membranes where receptors and effector-enzymes reside, while deactivating processes can be spread in the cytoplasm.…”
Section: Spatial Signaling By Gtpase Cascadesmentioning
confidence: 99%